2009
DOI: 10.1099/vir.0.013078-0
|View full text |Cite
|
Sign up to set email alerts
|

The genetic backbone modulates the phenotype of hepatitis B surface antigen mutants

Abstract: Hepatitis B virus (HBV) vaccine and diagnostic escape mutants are a growing concern. The principle target of detection, hepatitis B surface antigen (HBsAg), encoded by S, is completely overlapped by the reverse transcriptase encoding P. With the increased incidence of nucleos(t)ide analogue resistance altering P, the concurrent impact on S must be assessed. HBV DNA from 59 HBsAg-positive plasma samples was sequenced across the polymerase/surface region and the amino acid sequence of HBsAg was inferred. ELISAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In this study, 39% of mutations were mixtures of wild type and mutant amino acids and fall into this category. In addition, HBsAg antigenicity cannot always be inferred from the DNA sequence as genetic background at distant amino acid positions can play a role in “a” determinant structure and epitope recognition [24]. We observed that HBsAg epitope profiles did not always correlate with the DNA derived amino acid sequence, as has been noted by others previously [24].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In this study, 39% of mutations were mixtures of wild type and mutant amino acids and fall into this category. In addition, HBsAg antigenicity cannot always be inferred from the DNA sequence as genetic background at distant amino acid positions can play a role in “a” determinant structure and epitope recognition [24]. We observed that HBsAg epitope profiles did not always correlate with the DNA derived amino acid sequence, as has been noted by others previously [24].…”
Section: Discussionsupporting
confidence: 60%
“…In addition, HBsAg antigenicity cannot always be inferred from the DNA sequence as genetic background at distant amino acid positions can play a role in “a” determinant structure and epitope recognition [24]. We observed that HBsAg epitope profiles did not always correlate with the DNA derived amino acid sequence, as has been noted by others previously [24]. Despite these limitations, the combined use of serological and molecular methods allowed identification of immune escape mutants in Pakistani blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…Clonal sequence analysis of the HBV before and after parturition revealed that most cases analyzed expressed mutations in the Major Hydrophilic Region (MHR), from amino acid 120 to 160 of the small S protein, and the presence of minor S variants in the antigenic “a” determinant region. Mutations in the HBV “a” determinant region, as well as along entire S region, may affect antigenic conformation due to structural changes that alter antibody binding [ 16 , 31 34 ]. The identification of such immune escape variants may be important due to the risk of HBV vertical transmission despite complete passive-active immunoprophylaxis [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, all cases with HBV P gene mutations had concomitant S gene amino acid changes, including one patient (Case 6) with lamivudine resistance (rtM204I) that was associated with generation of a termination codon (UAG) in the S gene sequence. Recent studies have demonstrated that although the major antigenic binding epitopes of HBsAg may not be affected, distant mutations can modulate the a-determinant by influencing epitope conformation [45]. Further studies are needed on how these changes associated with antiviral resistance can affect the topology and antigenicity of the HBsAg.…”
Section: Discussionmentioning
confidence: 99%